2021
DOI: 10.4103/jfmpc.jfmpc_1516_20
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging role of non-physician health workers in prevention and control of non-communicable diseases in India

Abstract: Due to upsurge of non-communicable disease (NCD) burden, there is accentuated emphasis on task sharing and shifting NCDs-related health care delivery to non-physician healthcare workers especially nursing personnel and grass root level health professionals. This narrative review summates role of non-physician health workers, highlights various enablers and challenges while engaging them in delivery of NCD services so as to prevent and control various NCDs in India. Pubmed, Google scholar databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…However, in this study, HEWs had never been trained in hypertension. Participants in this study emphasized the importance of HEWs training for the successful implementation of HEWs’ home-based hypertension screening, which is consistent with research from Kenya [ 44 ], Ghana [ 45 ], Nepal [ 46 , 47 ], Bangladesh [ 48 ], China [ 49 ], and India [ 50 ]. A systematic review conducted in low and middle-income countries also found that non-physician health care workers training, as well as the provision of algorithms and screening protocols, are crucial for implementing task sharing strategy [ 51 ].…”
Section: Discussionsupporting
confidence: 82%
“…However, in this study, HEWs had never been trained in hypertension. Participants in this study emphasized the importance of HEWs training for the successful implementation of HEWs’ home-based hypertension screening, which is consistent with research from Kenya [ 44 ], Ghana [ 45 ], Nepal [ 46 , 47 ], Bangladesh [ 48 ], China [ 49 ], and India [ 50 ]. A systematic review conducted in low and middle-income countries also found that non-physician health care workers training, as well as the provision of algorithms and screening protocols, are crucial for implementing task sharing strategy [ 51 ].…”
Section: Discussionsupporting
confidence: 82%
“…This also underscores the need for ensuring adequate in-service training and continuous skill building for such cadres. Earlier studies have shown that continuous training is necessary and effective in improving clinical performance of non-physician cadres in PHC [ 31 , 44 ]. It is significant therefore that the national health mission in India has recently initiated programmes for in-service capacity building of CHOs [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASHAs and other CHWs have great potential to contribute to community-based health programs in LMIC and their involvement in such programs has been expanding recently in many countries such as Ethiopia, Bangladesh, and India ( 28 ). Patient screening, lifestyle education, support for self- management and assistance to navigate the health care system are tasks which can and have been successfully undertaken by CHWs for those with non-communicable diseases ( 9 , 29 ).…”
Section: Discussionmentioning
confidence: 99%